Příprava difuzních bariér s využitím technologie chemické depozice - Foltýnek, Jaroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství)
Tato diplomová práce se zabývá problematikou přípravy difuzních bariér technologií chemické depozice plynné fáze z práškových směsí. V teoretické části práce je řešena problematika přípravy difuzních vrstev pro tři nejběžněji používané způsoby přípravy, tj. CVD z práškových směsí, plynné a kapalné fáze. V praktické části práce je pak řešena problematika přípravy difuzních vrstev na superslitině Inconel 713LC metodou aluminizace z šesti různých práškových směsí probíhající za teploty 800°C po dobu 0, 2 a 5 hodin.

Masters thesis deals with formation of diffusion barrier coatings by means of powder mixtures chemical vapor deposition. Its theoretical part is focused on the problems with diffusion barriers formation, where predominantly three most commonly used methods are introduced, i.e. CVD from powder mixtures, active gasses and slurries. The experimental part of master thesis deals with the formation of nickel-aluminide diffusion barriers on Inconel 713LC superalloy substrate, where was for aluminization used six different powder mixtures at the temperature of 800 °C and dwell of 0, 2 and 5 hours.
Formation of Diffusion Barriers Using Chemical Vapour Deposition Process
Keywords: Aluminizace; Difuzní bariéry; Chemická depozice z práškových směsí; Inconel 713LC; Superslitina.; Aluminization; Diffusion barriers; Chemical vapor deposition from powder mixtures; Inconel 713LC; Superalloy.